Melt-processing of novel bioresorbable polymer nanocomposites for healthcare - Patel, Magdalena Maria (2019)
The load bearing capacity of biodegradable polymeric medical devices remains limited; an improvement in mechanical properties is desirable to widen the range of applications. Incorporation of nanoparticles via melt compounding is a route to improving mechanical properties, but appropriate processing routes are required to ensure the best outcome, achieving an optimum dispersion while minimising process-induced degradation. Various nanomaterials have been investigated for polylactic acid (PLA) reinforcement for orthopaedic applications; hydroxyapatite (HA), the main inorganic constituent of bone, is one of the most promising bioresorbable nanofillers. The principal focus of this work is the optimised processing of novel bioresorbable materials using scalable compounding techniques. The materials consist of: Resomer LR706S poly(L-co-D,L-lactide) (LR706S) PLA matrix from Evonik; novel nanoparticles of hydroxyapatite (HANP) with rod or platelet morphology, synthesised via a hydrothermal counter-flow process; dispersant coatings added in-situ onto HANP plates. The molecular dispersants consist of either purchased neat dodecenylsuccinic anhydride (DDSA) or bespoke short chained PLA with isosorbide head groups polymerised via a standard ring-opening route involving lactide, a tin catalyst and isosorbide initiator. Nanocomposites were processed in a laboratory scale twin-screw recirculating extruder HAAKE Minilab II, produced by Thermo Scientific, fitted with co-rotating conical screws. The materials were compounded in various conditions in order to establish processing parameters that provide an agreeable compromise between particles mixing and minimising the effect of polymer degradation. The produced materials were assessed by GPC, TGA, DSC, TEM, microCT, rheometry and flexural mechanical measurements. Three preferred compositions were selected to go forward to scaled-up manufacturing, using commercial processing facilities. Performed experiments showed that, beyond drying the polymer and fillers, drying of the bottled N2 (N2D) was essential to maintain high molecular weight of PLA, which in turn yielded high wall shear stress half-life time during compounding. The highest range of molecular weights was reported for HANP rod composites in N2D with the greatest Mw at 2.5 wt%. Additionally, molecular weight decreased with increasing amount of filler, regardless of the type of HANP. DSC measurements revealed that glass transition temperatures (Tg) for respective HANP rod and plate nanocomposites compounded in N2D were practically identical but higher than for the nanocomposites produced in Air. Furthermore, Tg of the nanocomposites was greater than the one measured for neat PLA and large changes of molecular weight were required (over 70% when compared to neat LR706S) to reflect it in the glass transition temperature of the material. The temperature at 5% weight loss for the compounded materials, measured in the TGA, was greater than for neat LR706S, and for HANP plates it was higher than for rods. Flexural properties were tested via three-point bending of miniature specimens and showed that modulus was independent of molecular weight over the considered range, while bending strength showed a small decrease with lowering Mw. The flexural strength and modulus were found to be higher for HANP plate nanocomposites compounded in N2D than mixed in Air, with the highest values shown for 10 wt% HANP rods in N2D. TEM image analysis was carried out with a semi-quantitative approach and revealed superior dispersion in 2.5 wt% HANP rod nanocomposites mixed in N2D when compared to other materials. This was confirmed by microCT measurements. Finally, the developed novel nanocomposites were successfully used in the production of demonstrator resorbable proximal pins and tensile bars by applying the optimised processes at scale on industrial equipment.